Motorcycle helmet - Part I. Biomechanics and computational issues - Shuaeib, F.M.; Hamouda, A.M.S.; R.S., Radin Umar; Hamdan, M.M.; Hashmi, M.S.J. (Elsevier Science, 2002)
This paper is devoted to review the current status related to motorcycle helmet crash studies from biomechanics and computational point of view. The importance of motorcycle helmet performance on statistical background was reviewed. The paper is divided into two main sections: in the first section, the biomechanics issues are highlighted and the head injury classifications are presented. The injury mechanisms for different injury types are analyzed and the related helmeted-head impacts were identified. The injury tolerances for the head main components presented with an insight into the current controversies among the different limits particularly rotational acceleration effects on the brain and the DAI brain damage type. In the second section, insights into the computational issues that are critical to the understanding of the helmet safety are presented. Some recent examples in which computational techniques used are also reviewed. Finally, directions for future research are also highlighted.